PASCAL Compiler HOW TO WORK FREE AND OPEN ON PPC386 - Sutarno Sutarno Sutarno (STMIK Jakarta, 2003)
Pascal is a procedural programming language including higher level languages, certainly can not be understood by the machine language so we need a software that will translate. It could be a software interpreter or compiler. For interpreters program will directly translated or executed, so that the program was not changing the shape and each instruction is what it is. While the compiler kesuatu transaction object shape and then by the linker and loader transformed into executable programs. At this time a lot of compiler that was developed to meet the supply needs of the programming language Pascal is no exception. Of course with different objectives and with the shortcomings and strengths of each. The goal is to provide a mini-howto to use and free pascal compiler optimization and provides an understanding of how the compiler creates an object-code compiler is roughly the same performance.